Computerised Applications and Evaluation Methods in Land Zoning - Cihan Ahmet Tutluoğlu; Vedia Dökmeci (European Regional Science Association (ERSA), 2005)
Land Zoning is an important issue in urban & regional planning, requiring heavy computational burden. Another challenge ihaving to decide on the parameters to be used in the evaluation. This paper takes the transportation-communication frequency and the rent-inflator interactions between different zonetypes (with possible coefficients) as the major elements in zone-evaluation. For the type of evaluation on the other hand three alternative methods were used. One of these methods only considers one-way interactions in rent-inflator relations. Another one is developped to include a self-updating mechanism on the same interactions. The third of the methods meanwhile attempts to take in account the topological factors. A software was developped in C++ that uses the Manhattan Metric to calculate the distances. The program prompts the user to feed in the evaluation method, different interaction coefficients as well as different landtypes and different maps. The software, based on the preference can either use a steepest descent heuristic or an enumeration algorithm.
Keywords: 330